INTEGRATED MARKETING COMMUNICATION (IMC) GREEN RADIO 96,7 FM PEKANBARU DALAM MEMBANGUN BRAND IMAGE SEBAGAI MEDIA BERBASIS LINGKUNGAN - Marbun, Tresia Br; ", Rumyeni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Integrated Marketing Communication (IMC) is the company's effort to integrate and coordinate all communication channels to deliver its message clearly, consistently and strongly influences its organization and products. Green Radio 96.7 FM Pekanbaru is the only electronic media that focuses on broadcasting news Environmental issues in Riau Province. This radio builds brand image as an environment-based media by choosing to use Integrated Marketing Communication (IMC). This study aims to find out Integrated Marketing Communication Green Radio 96.7 FM Pekanbaru in building brand image as an environment-based media.This research uses descriptive qualitative method. Technique of data collecting done by observation, interview and documentation. Objects studied are Direct Marketing, Interactive / Internet Marketing, Public Relations, and Personal Selling.Subjek amounted to 7 people.Teknik checking the validity of the data using the technique of elongation of participation and triangulation.Teknik determination of informants using purposive techniques.The result of this research is the activity of Direct Marketing Green Radiod in building brand image as an environment based media such as database management, telemarketing, sending program catalog and advertisement slot rate. Interactive activities are conducted using the website www.portalgreenradio.com, turn in applications in play stores, as well as through social media such as instagram, facebook and twitter.Aktivitas Public Relations include external activities and internal relations. Personal Selling activity is done by direct presentation to both client and resource person.Keywords: IMC, Brand Image, Green Radio 96.7 FM Pekanbaru